Evaluate the integral? : # int x^3e^(x^2) dx #

Answer 1

The answer is #=1/2e ^(x^2)(x^2-1) +C#

We need the integration by parts

#intp'qdx=pq-intpq'dx#

We perform the substitution

Let #u=x^2#, #=>#, #du=2xdx#

Therefore,

#intx^3e^(x^2)dx=1/2intue^ udu#

We apply the integration by parts

#p'(u)=e^u#, #=>#, #p(u)=e^u#
#q(u)=u#, #=>#, #q'(u)=1#

Therefore,

#1/2intue^ udu=1/2(ue^u-inte^udu)=1/2(ue^u-e ^u)#
#=1/2e ^(x^2)(x^2-1) +C#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

We seek:

# int \ x^3e^(x^2) \ dx = 1/2(x^2-1)e^(x^2) + C #

We seek:

# I = int \ x^3e^(x^2) \ dx #

Note as a helper that:

# d/dx ( e^(x^2) ) = 2xe^(x^2) iff int \ 2xe^(x^2) \ dx = e^(x^2) #

So we can write the integral as:

# 2I = int \ (x^2)(2xe^(x^2)) \ dx #

We can now use the formula for Integration By Parts (IBP):

# int \ u(dv)/dx \ dx = uv - int \ v(du)/dx \ dx #, or less formally # " " int \ u \ dv=uv-int \ v \ du #

I was taught to remember the less formal rule in word; "The integral of udv equals uv minus the integral of vdu". If you struggle to remember the rule, then it may help to see that it comes a s a direct consequence of integrating the Product Rule for differentiation.

Let # { (u,=x^2, => (du)/dx,=2x), ((dv)/dx,=2xe^(x^2), => v,=e^(x^2) ) :}#

Then plugging into the IBP formula:

# int \ (u)((dv)/dx) \ dx = (u)(v) - int \ (v)((du)/dx) \ dx #

gives us

# int \ (x^2)(2xe^(x^2)) \ dx = (x^2)(e^(x^2)) - int \ (e^(x^2))(2x) \ dx #
# :. 2I = x^2e^(x^2) - int \ 2xe^(x^2) \ dx + A # # " " = x^2e^(x^2) - e^(x^2) + A # # " " = (x^2-1)e^(x^2) + A #

Hence

# I = 1/2(x^2-1)e^(x^2) + C #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To evaluate the integral ∫x^3e^(x^2) dx, you can use the technique of integration by parts. Let u = x^2 and dv = x^3e^(x^2) dx. Then, differentiate u to get du = 2x dx, and integrate dv to get v = (1/2)e^(x^2).

Now, apply the integration by parts formula:

∫udv = uv - ∫v du

Substitute the values of u, dv, du, and v into the formula:

= (x^2)(1/2)e^(x^2) - ∫(1/2)e^(x^2) * 2x dx

Simplify:

= (1/2)x^2e^(x^2) - ∫xe^(x^2) dx

This integral can be solved by another substitution. Let w = x^2, then dw = 2x dx. This transforms the integral into:

∫xe^(x^2) dx = (1/2)∫e^w dw

Integrate:

= (1/2)e^w + C

Substitute w back in terms of x:

= (1/2)e^(x^2) + C

Now, put this result back into the first integral:

= (1/2)x^2e^(x^2) - (1/2)e^(x^2) + C

So, the integral of x^3e^(x^2) dx is (1/2)x^2e^(x^2) - (1/2)e^(x^2) + C, where C is the constant of integration.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7